Occupational Health and Safety Site Induction Training: An Insight into New Zealand’s Construction Industry - Poole, Kate Marie (Auckland University of Technology, 2023)
New Zealand’s construction industry has an extremely poor occupational health and safety (OHS) record. The industry consistently experiences comparatively high workplace fatalities and injuries, placing a significant financial and social burden on the affected individuals, their families, organisations, and the wider community. As legal intervention alone cannot improve such outcomes, other approaches, such as OHS training, are critical. Site inductions are one form of OHS training, focusing on introducing new employees, contractors, and visitors to the work environment, making them a vital component of integrating new workers within the workplace. OHS site induction training is crucial, as workers are at greater risk for work-related injuries during their first months of a new job. While some research is available on OHS training practices within New Zealand’s construction industry, there is a dearth of research on OHS site induction training. This gap is problematic as site induction training is typically the workers’ first on-site OHS experience. Therefore, this study explores the current state and effectiveness of OHS site induction training within New Zealand’s construction industry through the application of the Adult Learning Theory (ALT) and the Transfer of Training Theory (ToT). A mixed-methodology approach was applied in this study; a nationwide survey targeting construction workers within New Zealand was used in combination with stakeholder interviews. One hundred completed survey responses were gathered, and 12 stakeholders were interviewed. Data collected from the participants highlighted four key themes that impact OHS site induction training effectiveness: organisation, trainer, trainee, and training characteristics. As the findings of this study show, some assumptions and factors of ALT and ToT have been incorporated into the design and delivery of OHS site inductions, albeit not necessarily intentionally. However, there are still considerable areas for improvement. Notably, there needs to be a more significant focus on trainee engagement before, during, and after the induction process to ensure that the content and delivery are suitable for the intended audience and to promote a positive organisational safety culture. Doing so can aid in changing the perception of OHS site inductions as a ‘tick in the box’ compliance exercise and ensure workers feel their health, safety, and well-being are a priority. Another key finding was survey participants’ overwhelming preference for OHS site inductions to include some form of in-person interaction, with stakeholders recommending that online platforms be used only as a supplementary tool. This study has examined the current state and effectiveness of OHS site induction training within New Zealand’s construction industry through a broad lens. As such, this thesis has provided a general overview of the research area, indicating key trends rather than an in-depth examination of each influencing factor. Further research should be conducted on a larger scale, focusing on a smaller set of influencing factors. Specific areas that require further investigation include the feasibility of implementing a standardised approach to OHS site induction trainer qualifications to improve the quality of inductions delivered and using pre-site competency assessments to reduce the content and length of OHS site induction training.